2019
DOI: 10.1016/j.ynpai.2019.100037
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of paclitaxel-induced mechanical hypersensitivity and hyperalgesic priming with AMPK activators in male and female mice

Abstract: HighlightsPaclitaxel induces hyperalgesic priming in male and female mice.AMPK activators attenuate the development of hyperalgesic priming induced by paclitaxel.Narciclasine prevents and reverses paclitaxel-induced mechanical hypersensitivity and hyperalgesic priming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 45 publications
1
20
0
1
Order By: Relevance
“…In CIPN, for the protection of mitochondria, the inhibition of nitro-oxidative stress with novel potential drugs might also include the use of the mitochondrial protectant pifithrin-µ, which acts by inhibiting mitochondrial p53 accumulation [122,123], histone deacetylase 6 inhibitors [124], metformin [44,74,125], peroxynitrite decomposition catalysts [126], and antioxidants and anti-inflammatory cytokines, such as interleukin (IL) 10 [125,127] (Fig. 2).…”
Section: Future Outlook: Data From Preclinical Studiesmentioning
confidence: 99%
“…In CIPN, for the protection of mitochondria, the inhibition of nitro-oxidative stress with novel potential drugs might also include the use of the mitochondrial protectant pifithrin-µ, which acts by inhibiting mitochondrial p53 accumulation [122,123], histone deacetylase 6 inhibitors [124], metformin [44,74,125], peroxynitrite decomposition catalysts [126], and antioxidants and anti-inflammatory cytokines, such as interleukin (IL) 10 [125,127] (Fig. 2).…”
Section: Future Outlook: Data From Preclinical Studiesmentioning
confidence: 99%
“…Although metformin is able to activate AMPK at the same extent in neurons and microglia of male and female rats, this drug does not affect nerve injury-induced neuropathic pain in female rats. Authors suggest that this divergence could be due to the OCT2 expression between males and females (Inyang et al, 2019).…”
Section: Effects Of Metformin On Pain Neuropathic Painmentioning
confidence: 99%
“…These data add to the evidence that metformin induces its antiallodynic effects by reducing the aberrant translation induced by nerve injury. Of note, the effect of metformin in neuropathic pain is sexually dimorphic ( Inyang et al., 2019 ). Although metformin is able to activate AMPK at the same extent in neurons and microglia of male and female rats, this drug does not affect nerve injury-induced neuropathic pain in female rats.…”
Section: Effects Of Metformin On Painmentioning
confidence: 99%
“…A previous study in rats demonstrated that hyperalgesic priming to carrageenan does not occur in females (Joseph et al, 2003). Subsequent studies in mice and rats have shown additional sexual dimorphisms (Megat et al, 2018; Paige et al, 2018; Inyang et al, 2019), across the lifespan (Moriarty et al, 2019), but none of them have observed a similar absence of priming in female rodents. In fact, our work shows, at least with IL-6 as the priming stimulus, that the magnitude and duration of the response to PGE 2 given peripherally or intrathecally is longer in female mice than male mice.…”
Section: Discussionmentioning
confidence: 99%